Studenters erfaringer med Flipped Classroom i en helsefagutdanning - Tørris, Christine (Nordisk tidsskrift for helseforskning, 2015)
Background: The flipped classroom approach has gained increased attention in educational research literature. The purpose of this study was to investigate how students experience a flipped classroom approach in health education, compared to ordinary lectures. Method: Bachelor students (n=25) who watched the video-based material in the flipped classrooms pre-session, answered a questionnaire to evaluate their flipped classroom experience. The questionnaire consisted of both closed and open questions. Results: Ninety six per cent (24/25) of respondents found the video-based material in the pre-session useful. Seventy six per cent (19/25) of respondents found that the flipped classroom approach resulted in the highest learning outcome, over the traditional approach (16%, 4/25). Barriers to the flipped classroom approach was technical problems with the video-based material, such as screen view. Conclusion: The flipped classroom approach is promising as an acceptable approach for teaching in health science curricular in higher education.